The Dynamics of Work from Home (WFH): Examining the Impact of Job Motiva-tion, Mental Well-being, Work Environment, and Personality on Employee Produc-tivity - Waseem, Syeda Nazneen; Iqbal, Syeda Areej (Pakistan Journal of Humanities and Social Sciences, 2025)
The changing operating environment of working life and megatrends, such as digitaliza-tion, have strongly increased the proportion of time- and place-independent working methods in an expert organization in recent years. The study aims to examine the impact of job motivation, mental well-being, work environment, and personality on employee productivity. The data has been collected from a sample of 150 from the IT expert tar-geted population. The Smart PLS software has been used to analyse the data and conduct the operations. The five hypotheses are proven. It shares that the environmental ele-ments in the WFH setup have a positive impact on the productivity of work. All hypothesis proved that mental fitness increases in WFH setup that has a positive impact on the productivity of work. It shows that organizations can use work-from-home support in dealing with the challenges of the workplace and supporting better productivity. More communication skills and better use of alignment are needed.